Social marketing of the coffee cream liquor in the Association of Agroindustrial Entrepreneurs of Challohuma of San Juan del Oro - Huacani Sucasaca, Yudy (2024)
The purpose of the study is to explain the factors that determine social marketing of coffee cream liquor in the Association of Agroindustrial Entrepreneurs of Challohuma in San Juan del Oro District, Department of Puno (Southern Peru). The methodological design specifies a type of quantitative approach, with a non-experimental, cross-sectional design, through surveys in a total of 41 members of the association. Results demonstrated that the factors that significantly determine social marketing of coffee cream liqueur are marketing factors on individual consumers (product attributes, brand assignment, packaging, labeling and product support services), society (commitment to health, environment and collaborators), and about the company (internal quality of service, satisfied and productive service employees, greater service value, satisfied and loyal customers and healthy profits and growth). The Pearson coefficient r = 0.746 explains at the significance level of α = 0.01 that social marketing factors of coffee cream liquor of the Association of Agroindustrial Entrepreneurs of Challohuma in San Juan del Oro, are positively and considerably correlated with the factor of individual, social and business consumer, supporting the alternative hypothesis. It is concluded that social marketing plans must be implemented to boost the growth of the company.